1998
DOI: 10.1177/00220345980770090501
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning of S100 Calcium-binding Proteins from Bovine Periodontal Ligament and Their Expression in Oral Tissues

Abstract: The periodontal ligament (PDL) is a unique tissue that is crucial for tooth function. However, little is known of the molecular mechanisms controlling PDL function. To characterize PDL cells at the molecular level, we constructed a cDNA library from bovine PDL tissue. We then focused on the isolation of S100 calcium-binding proteins (CaBPs), because they mediate Ca2+ signaling and control important cellular processes such as differentiation and metabolism. We screened the PDL cDNA library with a mouse S100A4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
4
22
0
1
Order By: Relevance
“…It has been reported that, although S100A4 was only weakly expressed in dental papilla, dental follicle, and pulp tissue and not in gingival tissue, it was selectively and strongly expressed in PDL. In contrast, although S100A2 was not expressed in dental papilla, dental follicle, and pulp tissue, it was strongly expressed in both gingival tissue and PDL (17). Therefore, S1004A is more useful than S1002A for comparing the characteristics of gingiva and PDL, which is in agreement with previous report.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been reported that, although S100A4 was only weakly expressed in dental papilla, dental follicle, and pulp tissue and not in gingival tissue, it was selectively and strongly expressed in PDL. In contrast, although S100A2 was not expressed in dental papilla, dental follicle, and pulp tissue, it was strongly expressed in both gingival tissue and PDL (17). Therefore, S1004A is more useful than S1002A for comparing the characteristics of gingiva and PDL, which is in agreement with previous report.…”
Section: Discussionsupporting
confidence: 91%
“…Two S100 calcium-binding proteins, S100A4 and S100A2, were isolated from bovine periodontal tissues, and it was suggested that S100A4 might be a useful marker for distinguishing cells from the PDL and gingiva (17). It was also proposed that S100A4 had an extracellular role as a mineralization inhibitor, which is responsible for maintaining the periodontal ligament space (18).…”
mentioning
confidence: 99%
“…Interestingly Strutz et al 25) have isolated one S100 calcium-binding protein known as S100A4 as a fibroblast-specific protein and demonstrated its high gene expression in the periodontal mesenchyme during early stages of tooth morphogenesis in an in situ hybridization study. S100A4 might be a useful marker for distinguishing cells of the PDL from the gingiva 26) . S100A4 has an extracellular role as a mineralization inhibitor, which is responsible for maintaining the periodontal ligament space 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that S100 proteins, due to their Ca 2 þ -binding properties, are involved in regulating intracellular Ca 2 þ homeostasis or Ca 2 þ -dependent cell signalling (Boni et al, 1997;Duarte et al, 1998). In addition, an intracellular relocation of S100A4 upon treatment with thapsigargin has been reported (Mueller et al, 1999).…”
Section: Discussion Transcriptional Regulation Of S100a4mentioning
confidence: 99%